Wandering star - Russell, Romina (Russell, Romina. Zodiac novel, 2015)
Rho is ready to live a quiet life until Ochus appears to her, bearing a cryptic message that leaves her with no choice but to fight and she embarks on a journey through a new set of Houses that reveal much more about the Galaxy and herself.